PhD: The Amazing Journey - Volume 4 - Puteri Fadzline, Muhamad Tamyez (Penerbit UMPSA, 2024)
Our heartfelt appreciation extends to the Faculty of Industrial Management, particularly to our Dean, Dr. Mohd Hanafiah Ahmad, for the support given that enables this book to be published successfully. Our undying gratitude echoes towards our 12 esteemed authors; your remarkable stories form vibrantly on this literary canvas. Deep from your heart and soul, each of you have unfolded your strength for the ones you love. That is truly what passion is. To all readers, whether you have the intention to pursue, have just begun or are already on the challenging path of a PhD, we thank you. May this book shed light on every part of your PhD journey. Let passion guide you in the wonderful world of research and know that your journey reflects the strength of those who shared their experiences in these pages. Ultimately, our heartfelt thanks to the Almighty, the source of knowledge and wisdom, for His countless blessings and endless mercy that have guided this effort.